Strategi Bagian Protokol Setda Provinsi Sumbar Dalam Efektivitas Pelaksanaan Acara Pemerintah Provinsi Sumatera Barat - Ikhlas Wirayudha; Zike Martha (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the strategies implemented by the Protocol Division of the Regional Secretariat (Setda) of West Sumatra Province in ensuring the effectiveness of government event execution. Protocol, as a series of rules related to official events, plays a crucial role in ensuring events are conducted smoothly, orderly, and in compliance with established protocol standards. This research identifies various challenges faced by the Protocol Division, including social dynamics, technological advancements, and the demand for transparency and professionalism in the organization of government events. Using organizational communication theory, the study analyzes the role of protocol in managing communication and coordination among involved parties, including government officials, security, and the media. The findings show that well-planned strategies, effective coordination, and continuous evaluation are essential in creating a positive image for the local government, strengthening relationships among stakeholders, and enhancing the effectiveness of government event execution in West Sumatra Province.